Long-term multidisciplinary treatment including proton therapy for a recurrent low-grade endometrial stromal sarcoma and pathologically prominent epithelial differentiation: an autopsy case report - Osamu Maeda; Tetsuro Nagasaka; Makoto Ito; Tomoyo Mitsuishi; Fumihiko Murakami; Toshio Uematsu; Yukiko Hattori; Hiromitsu Iwata; Hiroyuki Ogino (BMC, 2020)
Abstract Background Long-term follow-up reports of low-grade endometrial stromal sarcoma (LGESS) including its clinical course and pathological data are rare. We previously reported the case of a Japanese woman diagnosed with LGESS, who was treated with multidisciplinary therapy. She had been suffering from uterine cervical tumor diagnosed as cervical polyps, or fibroid in statu nascendi, since 24 years old. The patient had survived for 25 years with the disease. This report presents her progress and pathological change since the previous report. Case presentation At age 45, the patient experienced a relapse of the remnant LGESS tumor between the right diaphragm and liver. Although chemotherapy was not effective, the tumor was eliminated by proton therapy. At age 46 years, the remnant tumors outside the irradiated field were resected. The disease was originally diagnosed as "neuroendocrine carcinoma (NEC)" using the surgical specimen. Therefore, cisplatin and irinotecan combination chemotherapy were administered to treat the remnant dissemination. After 4 cycles of chemotherapy, the liver metastases had enlarged and were resected surgically. Consequently, no remnant tumor was visible in the abdominal cavity at the end of the surgery. To determine the origin of NEC, we examined the previously resected specimens obtained from her ileum at age 40 years. A boundary between the LGESS and neuroendocrine tumor grade 2 (NET G2)-like lesion was found in the tumor, indicating that the origin of these tumors was LGESS. After less than 2 years of chemotherapy and undergoing surgery, a relapse of the tumor in the liver induced biliary duct obstruction with jaundice, which was treated with endoscopic retrograde biliary drainage. Although pazopanib prolonged her life for 10 months, she died from sepsis at age 49 years, which was caused by the infection that spread to the liver metastatic tumor via the stented biliary ducts. Autopsy revealed adenocarcinoma-like differentiation of the tumor. Conclusion This LGESS patient has survived for a long time owing to multidisciplinary treatment including proton therapy. The LGESS tumor differentiated to NET G2-like tissue and then further to adenocarcinoma-like tissue during the long-term follow-up.